Influence of Demographic Factors on Information-Seeking Behaviour of Medical Doctors in Teaching Hospitals in Nigeria (2020)
Information-seeking Behaviour (IB) of medical doctors is crucial to satisfying information needs relating to patients’ treatment and improvement of healthcare service delivery. Previous studies on doctors’ IB have focused largely on information sources and utilisation without consideration for factors predicting their IB; particularly Doctors’ Demographic Factors (DDF). This study, therefore, was designed to determine DDF (age, gender, marital status, specialty and medical job experience) as predictors of medical doctors’ IB in teaching hospitals in Nigeria. The survey design of correlational type was adopted and multi-stage procedure was used. Six teaching hospitals across five geo-political zones in Nigeria were randomly selected, excluding the North-east zone for safety reasons, while 13 medical specialties common to the hospitals were purposively selected. Five out of the 13 specialties were randomly selected and 20% of medical doctors in each of the selected specialties from each of the six hospitals were selected using the proportionate sampling technique, making a total of 668 medical doctors. The instruments used were DDF (α=0.73) and IB (α=0.69) scales and a structured interview was held with six highly experienced medical doctors, one representing each hospital. Data were analysed using descriptive statistics, Pearson’s product moment correlation and regression at 0.05 level of significance, while the qualitative data were content-analysed. Medical doctors’ age was 34.30 ± 3.60 years, and 61.6% were male. They were mostly married (66.3%) with 51.0% having 5-14 years of medical job experience. Their specialties were obstetrics and gynecology (24.6%), ophthalmology (23.4%), otolaryngology (21.1%), medicine (19.5%) and surgery (11.4%). The doctors’ specialty (r=-0.10), age (r=-0.10), gender (r=-0.11), job experience (r=0.06) had significant relationships with IB, while marital status did not. Specialty (β=0.15), age (β=0.06), job experience (β=0.04), gender (β=0.01) and marital status (β=0.01) relatively contributed to IB. Doctors’ specialty, age, gender and job experience influenced their information-seeking behaviour in teaching hospitals in Nigeria. These factors should be considered for improved information-seeking behaviour among medical doctors in teaching hospitals.